PENGARUH UMUR DAN UKURAN PERUSAHAAN TERHADAP ROE (Return On Equity)” (Studi pada Perusahaan Jasa Sektor Properti dan Real Estate yang Terdaftar di BEI Periode 2011 – 2017) - Sitio, Raston - (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
The problem under study is the influence of age and firm size on ROE (Return On Equity) and to determine whether there is a relationship between age and company size on ROE (Return On Equity). The data source used is secondary data found on the Indonesia Stock Exchange the Property and Real Estate sector service companies that are registered for seven consecutive years within the period of 2011 to 2017.The sampling technique uses purposive sampling, namely the sample selection technique using certain criteria. The analysis method used is descriptive analysis and classical assumption test. The analytical method for testing hypotheses is the regression and regression analysis that is selected is panel data regression using Eview 9 software program tools.From the results of the analysis it is known that there is a correlation of 0.2206 which shows a significant positive relationship between the age of the company with ROE (Return On Equity). As for the size of the company shows a negative relationship and does not affect ROE (Return On Equity. From the results of the determination analysis obtained coefficient of 0.9699 or 96.99% and 3.01% shows the magnitude of the contribution of other factors.